2010
DOI: 10.1021/je100042c
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Viscosities of Fatty Acid Methyl and Ethyl Esters

Abstract: To develop reliable models for the densities and viscosities of biodiesel fuel, reliable data for the pure fatty acid esters are required. Densities and viscosities were measured for seven ethyl esters and eight methyl esters, at atmospheric pressure and temperatures from (273.15 to 363.15) K. A critical assessment of the measured data against the data previously available in the literature was carried out. It is shown that the data here reported presents deviations of less than 0.15 % for densities and less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
216
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(245 citation statements)
references
References 42 publications
25
216
1
3
Order By: Relevance
“…Pratas et al obtained A = À5.7 Â 10 À4 MPa À1 [36] by fitting Eq. (10) to high pressure densities for laurate, myristate, and oleate methyl esters, reported by Pratas et al [55,56]. The Eq.…”
Section: Density Prediction 431 the Group Contribution Methods (Gcmentioning
confidence: 88%
See 2 more Smart Citations
“…Pratas et al obtained A = À5.7 Â 10 À4 MPa À1 [36] by fitting Eq. (10) to high pressure densities for laurate, myristate, and oleate methyl esters, reported by Pratas et al [55,56]. The Eq.…”
Section: Density Prediction 431 the Group Contribution Methods (Gcmentioning
confidence: 88%
“…With this extension (extended GCVOL) densities of tertiary alcohols, alkynes, carboxylic acids, allenes, cycloalkanes, fluorides, bromides, iodides, thiols, sulfides, sulfates, amines, nitriles, and nitro compounds were calculated with an average mean deviation of 1.5% for a database of 1040 compounds. Pratas et al [55,56] applied the original CGVOL to density prediction of pure FAMEs present in biodiesel in greater content, and those existing in minority. They concluded that for the majority FAMEs the density can be predicted within an ARD of 0.5%, except for the methyl linoleate since the model describes poorly the effect of unsaturation on density.…”
Section: Density Prediction 431 the Group Contribution Methods (Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 2). On the other hand, υ, CFPP and ρ are largely influenced by the degree of unsaturation [39,40]. Therefore, both saturation and unsaturation of FAMEs should have an optimal balance for high biodiesel quality.…”
Section: Scenedesmus Dimorphosmentioning
confidence: 99%
“…For instance, the cetane number and gross heating values are directly related to density and affect fuel efficiency [26][27][28]. Similarly, viscosity is an important parameter for development of fuels that governs the engine operation [29][30]. Surface tension is one of the vital PCP that directly affects fuel atomization due to cohesive forces and hence the biodiesel with higher surface tension values hamper the correct fuel atomization on an engine combustion chamber due to difficulty in small fuel droplet formation [31].…”
Section: Introductionmentioning
confidence: 99%